2008
DOI: 10.1111/j.1398-9995.2008.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal idiopathic rhinitis with local inflammatory response and specific IgE in absence of systemic response

Abstract: These results support the hypothesis that a subgroup of patients with IR have seasonal symptoms with evidence of a nasal allergic immune reaction in the absence of a positive SPT or serum specific IgE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
258
2
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(279 citation statements)
references
References 20 publications
8
258
2
11
Order By: Relevance
“…These patients have no serum-specific IgE, have negative skin and intradermal tests, and are categorized as LAR [2,3,6,9]. We believe that this is the first and only study of LAR in childhood as we could not find any such study in the English literature up toAugust 2013.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…These patients have no serum-specific IgE, have negative skin and intradermal tests, and are categorized as LAR [2,3,6,9]. We believe that this is the first and only study of LAR in childhood as we could not find any such study in the English literature up toAugust 2013.…”
Section: Discussionmentioning
confidence: 63%
“…There were no differences in the symptoms between the positive and negative NPT groups. Rondón et al [2] reported that posterior nasal secretion was the most common symptom in patients with idiopathic rhinitis and sneezing was the most frequent among patients with allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that an important number of patients previously diagnosed as nonallergic rhinitis had local allergy with nasal production of specific IgE and a positive response to a nasal allergen provocation test. [16][17][18] This entity has been suggested to be atopy 16 or local allergic rhinitis. 19 Patients with local allergic rhinitis do not have atopy so we detected negative skin-prick tests and normal serum-specific IgE levels, but these patients have similar symptoms of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%